An Investigation into the Non-bulk Rail Freight Transport in Australia - Hadi Ghaderi; Stephen Cahoon; Hong-Oanh Nguyen (Asian Journal of Shipping and Logistics, 2015)
In the last decade freight transport has gained further momentum in Australia, partly through significant demand growth at both domestic and international levels and partly as the result of Australia's long term need for infrastructure decision making. Amongst the freight task, non-bulk freight is the fastest growing freight task in Australia and is forecast to grow much faster than the rate of population growth and the average national GDP growth. However, rail's share in the non-bulk market has declined significantly in the last four decades. This study therefore provides an insight into the efficiency and operational management issues facing by the Australian non-bulk rail sector by focusing on three areas; the level of track compatibility and the relevant operational issues, the demographics of non-bulk freight in Australia and the current status of intermodal terminals in relation to rail connectivity and location. As the result, a more detailed understanding of the current shortages in the Australian non-bulk rail freight sector is achieved and managerial implications are provided.